2003
DOI: 10.1007/s00217-003-0694-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gluten-free flour mixes and fat powders on the quality of gluten-free biscuits

Abstract: Studies were conducted to develop gluten-free biscuits comparable in quality to wheat (W) biscuits and superior to those made from commercial gluten-free flour (Gf), suitable for coeliac sufferers. Three mixes of brown rice flour (R), corn starch (C), potato starch (P), soya flour (S), buckwheat flour (B) and millet flakes (M) were studied: RCPS in the percentage 70, 10, 10, 10, RPBM (50, 30, 10, 10) and RCPM (25, 25, 25, 25). Biscuits were tested for water activity, moisture, texture (snap test), diameter, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 12 publications
5
39
0
1
Order By: Relevance
“…Thus the type and percentage of encapsulating agent used and the quantity of fat and sugar content in the fat powders have a great influence on the biscuit quality. This study infers that there is some relation between dough characteristics and biscuits quality as observed by Schober et al (2003).…”
Section: Sensory Quality Of Biscuitssupporting
confidence: 66%
“…Thus the type and percentage of encapsulating agent used and the quantity of fat and sugar content in the fat powders have a great influence on the biscuit quality. This study infers that there is some relation between dough characteristics and biscuits quality as observed by Schober et al (2003).…”
Section: Sensory Quality Of Biscuitssupporting
confidence: 66%
“…In such products, there should be no traces of gluten proteins (Wieslander & Norbäck 2001a, Schober et al 2003, Størsrud et al 2003, Wijngaard & Arendt 2006a, Krahl et al 2008. Škrabanja et al (2001) reported that slow digestibiloity of proteins, due to the presence of polyphenols, prolong satiety in comparison to meals based on wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Gluten removal weakens dough structure to develop properly during kneading and baking (Gallagher, 2002). However, unlike pasta and bread, gluten network in cookies and biscuits requires minimum development (Schober et al, 2003). The texture of baked biscuits is primarily attributed to starch gelatinization and super cooled sugar rather than a protein/starch structure (Gallagher, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The texture of baked biscuits is primarily attributed to starch gelatinization and super cooled sugar rather than a protein/starch structure (Gallagher, 2002). Nevertheless, commercial gluten-free biscuits are generally based on pure starch, thus have poor organoleptic quality (Schober et al, 2003).Inadequate fiber intake from many GF foods had been reported as they are made with starches and /or refined flours with low content in fiber (Thompson, 2000). Studies on the nutritional composition of processed gluten-free demonstrated that they have high levels of lipids, sugars and salt.…”
Section: Introductionmentioning
confidence: 99%